Precis of the Phytochemical and Pharmacological Components of the Jungle Jalebi (Pithecellobium dulce) - Abdul Hameed; Yash Srivastav; Alka Verma (Pharmaceutical Research: Recent Advances and Trends Vol. 5, 2024)
The present review outlined the Phytochemical and Pharmacological Components of the Jungle Jalebi (Pithecellobium dulce). Pithecellobium dulce has numerous utilisations which has flexible jobs in the conventional arrangement of medication. The chemical compounds present in plants are used as antidiabetics, anticancer, anti-inflammation, etc. There are several allopathic medicines used in the treatment of diseases but they also have several side effects and drug interactions, so there is a need for herbal treatments that have lesser or no side effect. A few investigations are being directed concerning the viability of the entire plant or its parts for the treatment of various sicknesses and ailments. Triterpenoids, sterols, flavonoids, tannins, and phytocompounds like quercetin, kaempferol, and dulcitol were recognized from the different pieces of the plant. In this article, the different remedial properties of P. dulce have been shown. P. dulce is an evergreen sharp tree; each piece of the plant has huge healthful values. The pharmacological activities of various plant parts, such as their anti-diabetic, locomotor, immunizing agent venom, protease inhibitor, free radical searching, mitigating, anti-bacterial, anti-mycobacterial, abortifacient, spermicidal, anti-convulsant, anti-ulcer, anti-diarrheal, anti-tubercular, anti-tumour, and anti-oxidative properties, have been demonstrated. Safety studies, such as acute and sub-acute toxicity studies, have also demonstrated various pharmacological activities of plants. More examinations are required to investigate the utilisation of the plant for the commercialization of dynamic elements of organic and home-grown medication applications.